ANTIBACTERIAL AND ANTIOXIDANT ACTIVITY OF SAPONIN FROM ABUTILON INDICUM LEAVES - Ravi, Lokesh; V, Manasvi; B, Praveena Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Aim of this study is to analyze the antibacterial and antioxidant potential of crude saponin extract (CSE) from Abutilon indicum leaves. Methods: CSE was subjected for gas chromatography-mass spectrometry (GC-MS) analysis to identify its components. Antibacterial potential was analyzed using agar well diffusion method and minimum inhibitory concentration (MIC) was detected using 96-well plate method, against Staphylococcus aureus (MTCC: 3160) and Escherichia coli (MTCC: 443). DNA damage study was performed using comet assay. Antioxidant capability was studied using 2,2-diphenyl-1-picrylhydrazyl scavenging assay. Results: GC-MS analysis suggested a library match to benzene-1-4-bis(phenylmethyl), with a molecular weight of 258 g/mol to be the major component in the CSE at 21.25 RT. CSE demonstrated 96.16% free radical scavenging activity at 2.5 mg/ml concentration. CSE demonstrated a significant antibacterial activity in the well diffusion assay, S. aureus 17 mm and E. coli 15 mm, with a MIC value of 1.11 mg/ml. Comet assay demonstrated no DNA damage. Conclusion: These results conclude that CSE of A. indicum leaves possesses promising antibacterial and antioxidant potential. Keywords: Abutilon indicum, Saponin, Escherichia coli, Staphylococcus aureus, 2,2-diphenyl-1-picrylhydrazyl, Antibacterial assay.